Effect of Spring Back on Formation Process of Sheet Metal Bending Plates - Purwantono, Purwantono; Erizon, Nelvi; Helmi, Nofri; Akhbar, Muhammad; Muhibuddin, Muhibuddin (Universitas Negeri Padang, 2020)
This study aims to observe the amount of deviation that occurs due to the influence of spring back on the forming process. spring back in question is the back force when the plate undergoes a forming process, but when the load is released, the plate condition will reverse or return to its initial condition. This reversal is due to the factor of the elasticity of the material that is owned. Other factors that influence the bending process include thickness, width, angle of bending and others. object of this research is a sheet metal plate with a thickness of 1 mm - 4 mm. Forming process is done by bending process. This bending process is widely used in the plate forming process, namely to bend the sides of the plate to make it stiffer. This bending process is carried out in cold conditions where the process is carried out at room temperature. This research was conducted by preparing slices of the same width and length and then the process of bending them to form an angle of 20 ° to 120 °. results of this test indicate that the thicker the bent material has the tendency to produce small deviations. This means that the value of the spring back ratio also decreases. The value of the spring back ratio in this study ranges from 1% to 9%. This means that if the bending process is carried out on a steel plate with the resulting bending angle of 90 °, the bending angle of the shoe must be more than 90 °, the excess is 1 ° - 9 °. So that when the load is released, the position of the susdut bends closer to 90 °.